Introducing Digital Skills By Collaboration: A New Strategy to Develop Vital Digital Literacy Skills - Saxby, Donna (School librarian, 2018)
Most school librarians are familiar with pupils who seem technically competent but actually have very poor digital literacy skills. At KHS we have additional challenges due to under-utilization of technology in classroom teaching (particularly KS3), lack of BYOD taken up by pupils and a prohibition on the use of technology for homework (other than a few exceptions for sixth form). Having tried an approach of appointing a 'Digital Diva' in each department (a teacher overseeing DL for their subject) and unsatisfactory standalone DL classes for Year 9, a new strategy was needed to develop vital DL skills in our pupils. If teachers are able to provide me with content, I can slot in the digital skills with topics mirroring what pupils are doing in their subject rather than DL being an 'add-on'. The two departments that I have been working with this year are Geography and History.